(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the impact of digital transformation on the performance of Libyan Islamic banks. It begins by addressing the following main question: To what extent does digital transformation contribute to the performance of Libyan Islamic banks? The researcher adopted the descriptive and analytical approach in conducting the study, relying on a questionnaire as a tool for collecting data to achieve the study’s objectives.(110) questionnaires were distributed to the study sample, and (100) forms were retrieved. After examination and verification, (10) forms were excluded. Thus, the number of forms subjected to analysis was (90) forms. The study data was processed using the Statistical Package for Social Sciences (SPSS). The study reached many results, the most important of which were: There is a statistically significant relationship and impact between digital transformation and the performance of Libyan Islamic banks. Based on the most important findings, the study recommends that Libyan Islamic banks adopt a comprehensive digital transformation strategy that includes a clear vision and measurable objectives aimed at developing models for providing financial services and improving the quality of banking operations.